Original paperThe Abbott LCx-MTB assay is more sensitive than culture for detection of Mycobacterium tuberculosis in respiratory specimens - Krajewski, Wojciech; Kasielski, Marek; Król, Maciej; Białasiewicz, Piotr; Makówka, Agnieszka; Nowak, Dariusz (Archives of Medical Science, 2005)
Background: In countries with a high incidence of tuberculosis quick, reliable and cost effective testing for this disease is mandatory. With the introduction of new methods based on detection of amplificated DNA fragment (Abbott LCx Mycobacterium tuberculosis assay) re-evaluation of the diagnostic panel (smear, culture and BACTEC versus LCx) is needed. We conducted a prospective study comparing clinical usefulness of these tests in detecting Mycobacterium tuberculosis in respiratory specimens from four clinical settings mandating transfer of respiratory specimens. Material and methods: Respiratory specimens (320 sputum specimens and 54 bronchoalveolar lavage fluid specimens) collected from 374 patients under investigation for tuberculosis at the four clinical centers were divided into 2 portions. One portion was used for standard staining and cultures (auramine-fluorochrome and Ziehl-Neelsen staining, culture on Loevenstein-Jensen medium and in BACTEC Middlebrook 12B vials) and the second one was investigated for presence of Mycobacterium tuberculosis with LCx -MTB assay. Results: In patients with a final diagnosis of tuberculosis we found LCx test more sensitive than culture and bacterioscopy (93.3% versus 81.3%; p<0.01 and 41.0%; p<0.001, respectively); while there was no difference in specificity and negative predictive value between LCx and culture. Conclusions: LCx test is an effective diagnostic tool in the setting of the central laboratory to cooperate with different, distant, clinical centers for detection of Mycobacterium tuberculosis in respiratory specimens from subjects belonging to a population with a high incidence of tuberculosis.